BNIP3 Upregulation Characterizes Cancer Cell Subpopulation With Increased Fitness and Proliferation - Zhu, Yanyan; Chen, Bowang; Yan, Junya; Zhao, Wendi; Dou, Pengli; Sun, Na; Wang, Yaokai; Huang, Xiaoyun (Frontiers in Oncology, 2022)
BNIP3 is a BH3 only protein with both pro-apoptotic and pro-survival roles depending on the cellular context. It remains unclear how BNIP3 RNA level dictates cell fate decisions of cancer cells. Here we undertook a quantitative analysis of BNIP3 expression and functions in single cell datasets of various epithelial malignancies. Our results demonstrated that BNIP3 upregulation characterizes cancer cell subpopulations with increased fitness and proliferation. We further validated the upregulation of BNIP3 in liver cancer organoids compared with 2D culture. Taken together, the combination of in silico perturbations using public single cell datasets and experimental cancer modeling using organoids ushered in a new approach to address cancer heterogeneity.